2020
DOI: 10.1186/s40337-020-00338-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting maladaptive overcontrol with radically open dialectical behaviour therapy in a day programme for adolescents with restrictive eating disorders: an uncontrolled case series

Abstract: Background Radically Open Dialectical Behaviour Therapy (RO-DBT) was developed to target maladaptive overcontrol, a proposed core difficulty of restrictive eating disorders. RO-DBT is now the main group treatment model at the Intensive day Treatment Programme (ITP), Maudsley Hospital. This ITP case series aimed to investigate whether overcontrol is associated with restrictive eating disorder symptoms in adolescents and to evaluate ITP outcomes since RO-DBT skills classes were introduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 70 publications
(82 reference statements)
2
33
0
Order By: Relevance
“…Similarly, adolescents report improvements in emotion regulation, emotional expression, cognitive flexibility, attachment relationships and social functioning at end of treatment ( 69 , 71 ), although cognitive flexibility did not improve after a brief 4-week cognitive remediation group offered within the DP context ( 70 ). Significant improvements in self-esteem have been reported ( 67 , 71 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, adolescents report improvements in emotion regulation, emotional expression, cognitive flexibility, attachment relationships and social functioning at end of treatment ( 69 , 71 ), although cognitive flexibility did not improve after a brief 4-week cognitive remediation group offered within the DP context ( 70 ). Significant improvements in self-esteem have been reported ( 67 , 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the available data, it has been consistently reported that DP treatment is associated with improvements in symptoms of depression ( 35 37 , 48 , 56 , 58 , 62 , 64 , 69 , 73 ), as well as anxiety and worry ( 36 , 48 , 58 , 59 , 62 , 71 , 73 ). There are some individual differences between studies in the pattern of improvements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations